Conducting Fibers: Downsized Sheath–Core Conducting Fibers for Weavable Superelastic Wires, Biosensors, Supercapacitors, and Strain Sensors (Adv. Mater. 25/2016). Issue 25 (3rd July 2016) - Wang, Hongyan; Liu, Zunfeng; Ding, Jianning; Lepró, Xavier; Fang, Shaoli; Jiang, Nan; Yuan, Ninyi; Wang, Run; Yin, Qu; Lv, Wei; Liu, Zhongsheng; Zhang, Mei; et al.
Abstract : Using intelligent textiles for clothing represents one possibility for weavable superelastic conducting fibers that can store energy, sense body motions, and detect biochemicals. On page 4998, S. Yin, R. H. Baughman, and co‐workers demonstrate that these hair‐like‐diameter fibers, comprising buckled carbon nanotube sheaths on a rubber core, can be used as glucose sensors, supercapacitors, ultrafast strain sensors, and electrical interconnectors. The performance of these structures is maintained also under giant strain.